Between Aspiration and Apathy: Shifting Scale and the "Worlding" of Indigenous Day of the Dead Music. (26th May 2016) - Faudree, Paja
Abstract: This article examines Mazatec Day of the Dead music, a popular musical form featuring lyrics in the indigenous Mexican language Mazatec, which has become popular online and off, with some practitioners even dreaming of global prominence. I use the tension between musical aspirations and apathy to illuminate how the creation of "world musics" and other popular forms depends on unstable recalibrations of scale, including "shrinking" tendencies when aimed at particular local audiences. Ultimately, I suggest the shifting dynamics of scale is a key vehicle through which competing frames of belonging become expressed.